Illustrated cabinetmaking : how to design and construct furniture that works - Hylton, William H. (Fox Chapel Pub., 2008)
Design and construct furniture that works with the help of the most complete visual guide ever published. It's all here: ideas and inspiration, standards, options and alternatives, construction solutions, plans.